Radically insensitive theists - Kirk-Giannini, Cameron Domenico (Religious studies, 2019)
Sceptical theists attempt to meet the challenge to theism posed by evidential arguments from evil by appealing to the limitations of human cognition. Drawing on an exchange between William Rowe and Michael Bergmann, I argue that consistent sceptical theists must be radically insensitive to certain kinds of evidence about prima facie evils - that is, that they must endorse the claim that not even evidence of extreme and pervasive suffering could justify disbelief in theism. I show that Bergmann's attempt to respond to this problem does not succeed and argue that no alternative response is forthcoming, concluding that the threat of radical insensitivity constitutes a serious and underappreciated difficulty for sceptical theism.